Особливості запилення та насіннєутворення деяких видів рододендрона при інтродукції в Правобережному Лісостепу України - Vegera, L.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
The characteristics of the seed-formation ability of 14 rododendron species introduced under the conditions of the Right-Bank Forest-Steppe Zone of Ukraine are given in the paper. Major critical periods in the development which affect the seeds formation ability of rododendrons are determined. Main factors which have a negative effect on pollination and seed formation under introduction are found. The characteristics of seed productivity, quality characteristics of seeds, produced by rododendrons in dendropark "Sofiivka", are presented in the paper.